Evaluasi Efektivitas Autodesk Revit Berbasis Building Information Modeling (BIM) sebagai Media Pembelajaran pada Pendidikan Desain Pemodelan Bangunan di Sekolah Menengah Kejuruan - Putu Sri Aryudihati; Kadek Rihendra Dantes; I Made Yudana (SCHOULID: Indonesian Journal of School Counseling, 2025)
Conducted at SMK Negeri 1 Denpasar, the study involved 213 Grade XI and XII students of the DPIB program, with samples selected through stratified random sampling. A program evaluation design was employed, utilizing a Likert-scale questionnaire as the primary instrument, supported by interviews, observation, and documentation. Data were analyzed using descriptive quantitative techniques. The findings indicate that the implementation of Autodesk Revit as a BIM-based learning medium is generally effective across the context, input, process, and product dimensions, with the overall program categorized as highly effective. The evaluation reveals that institutional readiness, instructional planning, learning implementation, and student learning outcomes are aligned with the intended objectives of BIM integration in vocational education. However, several challenges were identified, including limited student understanding of BIM concepts, disparities in hardware specifications, varying levels of ICT competence, time constraints, and the technical complexity of the software. To address these challenges, the school implemented strategies such as strengthening foundational BIM concepts, optimizing infrastructure, utilizing Autodesk educational licenses, providing mentoring and remedial support, applying staged project-based learning approaches, and offering continuous feedback. Overall, the study demonstrates that the structured integration of BIM through Autodesk Revit, when supported by adequate planning and institutional commitment, can enhance the quality of vocational building design education. The findings contribute to the development of evidence-based evaluation practices for BIM implementation in vocational education contexts